2001
DOI: 10.1046/j.1464-5491.2001.00446.x
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged QTc interval predicts mortality in patients with Type 1 diabetes mellitus

Abstract: QTc prolongation, but not increased QT dispersion, is an independent marker of increased mortality in patients with Type 1 diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
133
1
6

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(147 citation statements)
references
References 24 publications
(32 reference statements)
7
133
1
6
Order By: Relevance
“…To our knowledge, this is the first study to prospectively assess the role of QT c and rHR in both types of diabetes within the same study framework. Its findings confirm the prognostic value of QT c as an independent risk factor for all-cause mortality in type 1 diabetes [5,[28][29][30]. In addition to the results of Rossing et al [5], the present…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…To our knowledge, this is the first study to prospectively assess the role of QT c and rHR in both types of diabetes within the same study framework. Its findings confirm the prognostic value of QT c as an independent risk factor for all-cause mortality in type 1 diabetes [5,[28][29][30]. In addition to the results of Rossing et al [5], the present…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, it also reproduced the findings of Sawicki and colleagues, which were made in subjects with nephropathy [28] in a more general sample of subjects with type 1 diabetes. The HR for overall mortality found in the present analysis was comparable to that in Rossing's report [5], but tended to be lower than the risk ratio found in subjects with overt nephropathy [28] (1.10 and 1.47 per 10 ms, respectively). Earlier reports have suggested that the association between QT c and cardiovascular disease was stronger in male than in female subjects with type 1 diabetes [30].…”
Section: Qtc Intervalsupporting
confidence: 74%
See 1 more Smart Citation
“…Clinically, there are several inherited and acquired conditions, including diabetes,4, 5, 9, 10, 12, 13 that are characterized by prolongation of the QT interval, a factor that enhances the incidence of ventricular arrhythmia and sudden cardiac death 14. Moreover, increased dispersion of ventricular repolarization occurs in diabetic patients5, 6, 7, 8, 10 with an important implication on propensity to develop electrical disturbances 4, 13, 15, 16.…”
Section: Resultsmentioning
confidence: 99%
“…Prolongation of the QT interval and increased dispersion of repolarization have been observed in the diabetic population,4, 5, 6, 7, 8, 9, 10 and these variables, together with intervening comorbidities,11 represent critical substrates for the occurrence of electrical disturbances 4, 12, 13, 14, 15, 16, 17. But whether alterations at the cellular level contribute to protracted electrical recovery and repolarization variability with diabetes remain to be determined.…”
Section: Introductionmentioning
confidence: 99%